Datenreport Erziehungswissenschaft 2020 Erstellt im Auftrag der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Abs, Hermann Josef; Kuper, Harm; Martini, Renate (Schriften der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE), 2020)
The data report presents the structural development of educational science and is commissioned every four years by Deutsche Gesellschaft für Erziehungswissenschaft (DGfE). The publication aims to inform the field-specialized public, education and higher education politics as well as the public about current developments in educational science as one of the largest fields at German universities. Particular attention is paid to study programs, students, degrees, human resources, research achievements and the promotion of young talents. The data report provides basic information on how educational science develops under the influence of recent changes and identifies the need for action in terms of the political field as well as higher education and education policy. Relevant information in the data report - for example on students, degrees and academic careers - is differentiated by gender. The DGfE thus fulfills its own claim to support gender equality. The data report is of particular importance for current discussions about securing training capacities for professional pedagogical professions and about academic careers. ; Der Datenreport ist eine regelmäßig alle vier Jahre von der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) in Auftrag gegebene Darstellung struktureller Entwicklungen der Erziehungswissenschaft. Er informiert die Fachöffentlichkeit, die Bildungs- und Hochschulpolitik sowie die Öffentlichkeit über Trends und den jeweils erreichten Entwicklungsstand der Erziehungswissenschaft als eines der größten Fächer an deutschen Hochschulen. Besonderes Augenmerk liegt auf den Indikatoren zu Studiengängen, Studienabschlüssen, Personal, Forschungsleistungen und Nachwuchsförderung.